The relationship between training and development and organizational peformances at Majlis Daerah Jerantut / Nurul Aini Che Cob and Nor Amirah Juhari - Che Cob, Nurul Aini; Juhari, Nor Amirah (Faculty of Business and Management, 2013)
The purpose of this study is to find out the factor of training and development that gives impact on organizational performance in Majlis Daerah Jerantut. There are two objective for this research first is to investigate the relationship between training and development and organizational performances. Second objective is measure the level of Training and Development, a) training design, b) on the job training, and c) delivery style and Organizational Performances. The hypothesis are developed from this research first, there is a relationship between training design and organizational performances. Second there is a relationship between on the job training and organizational performances, next here is a relationship between delivery style and organizational performances. Lastly, there is a relationship between training and development and organizational performances. The target of population was the employees of Majlis Daerah Jerantut. The respondent taking was only 50 workers of Majlis Daerah Jerantut which is only the upper management or inside worker. Therefore, the sample for our study is only 48 workers of Majlis Daerah Jerantut. Reliability analysis was used to measure the consistency of variable. Correlation analysis is used to identify the relationship between the variables and descriptive analysis is used to measure the level of independent variable and dependent variable. The finding show that, there are moderate and strong relationship between training and development (training design, on the job training, delivery style). The others finding show that, the level of training and development (training design, on the job training, delivery style) and organizational performance was high. This clearly indicated that Majlis Daerah Jerantut have high level of training and development and organizational performance. From the research that has been done, there are several recommendations for the Managers and Organization first, biasness should be minimized while selecting the candidates for training. Second, employees should be clearly communicated about the potential benefits of training programs and lastly, Choose the right trainer.